CREATING CUSTOMER RETENTION THROUGHT CUSTOMER INCENTIVES, TRUST AND COMPLAINT HANDLING (AT BMT AMANAH UMMAH IN KARTASURA) - Yona Septi Kartikawati; Istiatin Istiatin; Sri Hartono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine and explain the simultaneous and partial influence of customer incentives, trust and complaint handling on customer retention at the BMT Amanah Ummah in Kartasura. This research method uses quantitative descriptive research design. With a population of 1.500 respondents. Withdrawal of the number of samples is determined by the Slovin formula and the results are 100 respondents. Sampling technique uses Instidental Sampling. Data collection using a questionnaire. Data analysis techniques used statistical analysis are multiple linear regression test, F test, t test and coefficient of determination. The results showed that customer incentives, trust and complaint handling simultaneously and significantly affected customer retention at the BMT Amanah Ummah in Kartasura. Customer incentives have a positive and significant effect on customer retention in the BMT Amanah Ummah in Kartasura. Trust has a positive and significant effect on customer retention in the BMT Amanah Ummah in Kartasura. Complaint handling has a positive and significant effect on customer retention at the BMT Amanah Ummah in Kartasura. The coefficient of determination or contribution of variable customer incentives, trust and complaint handling to customer retention in the BMT Amanah Ummah in Kartasura is 50.4%. Suggestions from this research, BMT Amanah Ummah should in this case continue to improve and pay attention to factors that influence customer retention, namely customer incentives, trust and complaint handling.